ESMO Consensus Conference on malignant lymphoma: general perspectives and recommendations for the clinical management of the elderly patient with malignant lymphoma. (29th November 2017) - Buske, C; Hutchings, M; Ladetto, M; Goede, V; Mey, U; Soubeyran, P; Spina, M; Stauder, R; Trněný, M; Wedding, U; Fields, P; ,
Abstract: The European Society for Medical Oncology (ESMO) consensus conference on mature B cell lymphomas and chronic lymphocytic leukaemia (CLL) was held on 20 June 2015 in Lugano, Switzerland, and included a multidisciplinary panel of 25 leading experts. The aim of the conference was to develop recommendations on critical subjects difficult to consider in detail in the ESMO Clinical Practice Guidelines. The following areas were identified: (1) the elderly patient, (2) prognostic factors suitable for clinical use, and (3) the 'ultra-high-risk' group. Before the conference, the expert panel was divided into three working groups; each group focused on one of these areas in order to address clinically-relevant questions relating to that topic. All relevant scientific literature, as identified by the experts, was reviewed in advance. During the consensus conference, each working group developed recommendations to address each of the four questions assigned to their group. These recommendations were presented to the entire panel and a consensus was reached. This consensus, which was further developed in continuous post-meeting discussions, formed the basis of three manuscripts, each covering one of the three key areas identified. This manuscript presents the consensus recommendations regarding the clinical management of elderly patients diagnosed with malignant lymphoma. Four clinically-relevant topics identified by the panel were: 1) how to define patient fitness, 2) assessing quality of life, 3) diagnostic work-up and 4) clinical management of elderly patients with lymphoma. Each of these key topics is addressed in the context of five different lymphoma entities, namely: CLL, follicular lymphoma, mantle cell lymphoma, peripheral T-cell lymphoma and diffuse large B-cell lymphoma. Results, including a summary of evidence supporting each recommendation, are detailed in this manuscript.